Suplementasi Ekstrak Asam Kandis (Garcinia xanthochymus) dalam Air Minum terhadap Kadar Malondialdehid Kuning Telur dan Komposisi Kimia Daging dan Telur Puyuh: Supplementation of Garcinia xanthochymus Extract on Water to Malondialdehid Content of Egg Yolk and Chemical Composition of Quail Meat and Eggs - W U Cahyani; A Darmawan; dwi margi suci (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2021)
The purpose of this study was to evaluate the effect of supplementation of Garcinia xanthochymus extract in drinking water on the quail meat and eggs quality (fat content, protein content) and malondialdehyde (MDA) on egg yolk. This study used female quails (132 tails) aged 42 days, which were kept for 6 weeks, and then divided into four groups treatments of drinking water, and 3 replications each treatment. The method used was a Completely Randomized Design (RAL) with P0 (control), P1 (pH 4), P2 (pH 3), P3 (pH 2). The variables observed were moisture content, crude fat content and crude protein content in quail meat and eggs but MDA only on yolk eggs. The results showed a significantly decreased (p<0.05) effect of Garcinia xanthochymus extract supplementation in drinking water on MDA levels of yolk quail eggs. However it had no significant effect on moisture content, crude fat content, and crude protein content in yolk quail eggs . The treatments had significantly increased crude protein in meat. It was concluded that giving extract of Garcinia Xanthochymus extract (kandis acid) at pH 2 in drinking water decreased the MDA content of quail egg yolks. Key words: antioxidant, Garcinia Xanthochymus, chemical compound of meat and egg, egg yolk MDA